Hydrological controls on the biogeochemical dynamics in a Peruvian mangrove forest - Pérez, Alexander (2017)
This study was carried out within the framework of the project: “Impacto de la Variabilidad y Cambio Climático en el Ecosistema de Manglares de Tumbes”. Supported by the International Development Research Centre (IRDC) of Canada under management of the Instituto Geofísico del Perú (IGP), in cooperation with the Instituto del Mar del Perú (IMARPE) and the Universidad Peruana Cayetano Heredia (UPCH). The authors acknowledge the program Cátedra CONCYTEC en Ciencias del Mar, which supported the realization of this thesis as well. Detailed geochemical analyses were supported by the IRDC and by the project MINIOX (IMARPE), and were performed in the Marine Geology Laboratory of IMARPE and in the Marine Science Laboratory of UPCH. CJS is supported by the Australian Research Council (DE160100443, DP150103286 and LE140100083). We would like to thank our colleagues Luis Quipuzcoa, Ernesto Fernández, Wilson Carhuapoma, Percy Montero, Rubén Alfaro, Manuel Vera, and Bruno G. Libardoni, without their help this study would not have been possible. We also are grateful to Dr. Ken Takahashi, Douglas Tait and Dr. Wilson Machado, who provided us with invaluable suggestions since the early stage of this study.